The Utilization of Coal 4200 Calories Using Value-Added Method and Capital Budgeting Technique For Economic Evaluation - Sitohang, Pesta Ferdinan; Aldianto, Leo (The Indonesian Journal of Business Administration, 2015)
Abstract. Coal is an alternative energy derived from vegetation which are buried in the ground for millions of years ago and become rock. The changing of vegetation into the rocks was done by natural with supporting factors such as burial depth, time length of the burial, temperature and pressure in certain depth and also the type of vegetation. The embodied energy comes from the absorption of energy millions years ago by vegetation. Based on quality, coal divided into two main categories. The first category is low rank coal (lignite, sub-bituminous) and the second is hard coal (bituminous and anthracite). This categorization is based on the carbon quantity/component in the coal. PT Trisensa Mineral Utama is a mining company that established from 2004 and starts its production in Sanga-Sanga, East Kalimantan at the end of 2011. Produce coal with 4200 GAR for the first time, PT Trisensa Mineral Utama sold its coal to Hongkong, China, India, Japan, South Korea, etc. PT Trisensa Mineral Utama is a sister company of PT Toba Bara Sejahtra , together with PT Indomining, and PT Adimitra Baratama Nusantara, listed in Jakarta stock exchange since July 6, 2012. The golden era of coal occupied until 2011, where the mining industry enjoys the big margin; while more and more competitors (producer) or new comers and contractor was emerged, from small to big scale. After 2011, the coal price headed to its equilibrium value, causing a lot of players who do not have experience and strong capital into bankruptcy. As the root cause of the problem is that the production cost exceeds the sale price. This condition applied to the two coal category, especially low rank coal (lignite and sub-bituminous). PT Trisensa Mineral Utama which previously had 4200 GAR coal products, move to produce 4800 GAR and 5600 GAR coal. In the end the 4200 GAR coal is abandoned because it cannot give economic value to the organization. Seeing this problem, there is a need of innovation for its coal product. It can be achieved if carried out an increase in value-added products. Coal with 4200 GAR can be used for several types of value added services such as coal to liquid (Liquefaction), coal to gas (gasification), coke, as well as into electric through power generation. Based on existing conditions and needs, the possible solution is the use of coal for generating electricity. This is influenced by the production cost which should be less than the selling price. The evaluation is conducted by using economic analysis based on the capital-budgeting-technique (NPV, IRR, PP), where the results give a positive tone.The solution will necessarily require human resources and finance. Associated with the existing regulation Pasal 5 (1,2,3) Permen ESDM No. 10 Tahun 2014, PT Trisensa Mineral Utama need to form a consortium with another organization/company to establish a new entity for power plant company. The success of the implementation of this solution is very dependent on the readiness and seriousness PT Trisensa Mineral Utama as a major shareholder.Â Keywords: capital-budgeting-technique, coal value added, power plant